Sincronização de receptoras no diestro para utilização em programa se transferência de embriões em equinos - Souza, Renata Tenório Ribeiro de [UNESP] (2014)
Several factors influence the outcome of embryo transfer (TE) in horses, and the synchrony between donor and recipient often limits the use of the recipient, because there is no synchronization of the uterine environment and the stage of the embryo to be transferred. Mares embryo donors often due to different handling of the recipients tend to have longer ovulatory cycles during the breeding season. Currently many protocols and therapies enable greater recovery of embryos per cycle, even old mares, so the receivers play an important point in the chain of TE. Several strategies are used to maximize the use of recipient mares and thereby increase the number of products per season TE. With the intention of increasing or synchronize the time of use of the receiver during the breeding season may be mentioned progesterone and progestins, estrogens and thus reduces the ratio donor / recipient, resulting in a reduction of cost and time, besides the use mares with ciclantes not satisfactory pregnancy rates. The present study aimed to study the effect of the use of estrogen and progesterone in diestrus to maximize the use of embryo recipients in TE programs